Evaluation of Comprehensive Chromosome Screening Platforms for the Detection of Mosaic Segmental Aneuploidy. Issue 2 (February 2019) - Goodrich, David; Xing, Tongji; Tao, Xin; Lonczak, Agnieszka; Zhan, Yiping; Landis, Jessica; Zimmerman, Rebekah; Scott, Richard T.; Treff, Nathan R.
Abstract : (Abstracted from J Assist Reprod Genet 2017;34:975–981) Advancements in the efficacy of comprehensive chromosomal screening (CCS), namely, the ability to detect aneuploidy in all 24 human chromosomes, have established it as a cornerstone of infertility care. Recently, the development of high-throughput, massively parallel sequencing for use with CCS has led to highly accurate, simultaneous screening of multiple samples.